More Education Does Make You Happier – Unless You Are Unemployed - Alexander Bertermann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2023)
This paper investigates the causal effect of education on life satisfaction, exploring effect heterogeneity along employment status. We use exogenous variation in compulsory schooling requirements and the build-up of new, academically more demanding schools, shifting educational attainment along the entire distribution of schooling. Leveraging plant closures and longitudinal information, we also address the endogeneity of employment status. We find a positive effect of education on life satisfaction for employed individuals, but a negative one for those without a job. We propose an aspiration-augmented utility function as a unifying explanation for the asymmetric effect of education on life satisfaction.
Keywords: I26; I31; C26; 330; education; life satisfaction; employment status; compulsory schooling reforms; school openings; instrumental variable estimation